Epigenetic Control of Muscle Stem Cells: Focus on Histone Lysine Demethylases - Cicciarello, Delia; Schaeffer, Laurent; Scionti, Isabella (Frontiers in Cell and Developmental Biology, 2022)
Adult skeletal muscle is mainly composed of post-mitotic, multinucleated muscle fibers. Upon injury, it has the unique ability to regenerate thanks to the activation of a subset of quiescent muscle stem cells (MuSCs). Activated MuSCs either differentiate to repair muscle, or self-renew to maintain the pool of MuSC. MuSC fate determination is regulated by an intricate network of intrinsic and extrinsic factors that control the expression of specific subsets of genes. Among these, the myogenic regulatory factors (MRFs) are key for muscle development, cell identity and regeneration. More globally, cell fate determination involves important changes in the epigenetic landscape of the genome. Such epigenetic changes, which include DNA methylation and post-translational modifications of histone proteins, are able to alter chromatin organisation by controlling the accessibility of specific gene loci for the transcriptional machinery. Among the numerous epigenetic modifications of chromatin, extensive studies have pointed out the key role of histone methylation in cell fate control. Particularly, since the discovery of the first histone demethylase in 2004, the role of histone demethylation in the regulation of skeletal muscle differentiation and muscle stem cell fate has emerged to be essential. In this review, we highlight the current knowledge regarding the role of histone demethylases in the regulation of muscle stem cell fate choice.